PERAN PENTING PENDIDIKAN DALAM TRANSMISI FILSAFAT YUNANI KE DUNIA ISLAM - Hasan Ruzakki; Noviasari Maimunah (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
The encounter of Greek philosophy and the Islamic paradigm produce a glorious civilization in the Islamic world. Furthermore, Islamic civilization became the center of the science development and was visited by a number of Western scholars to enhance knowledge. In addition to the Qur'an and hadith, one aspect of science that is no less important in the Islamic advancement is philosophy. A few indicators supporting the entry of Greek philosophy into the Islamic world include the establishment of a magnificent library, baitul hikmah, and the association of Muslim scholars who founded the first institute. Which are the shoots of the most urgent education post the establishment of the Alexandria Museum.